Effects of Productivity, R&D and Income Inequality on Economic Growth: An Empirical Estimation Using Panel Data - Hakan Yıldırım; Hakan Aydoğan (Verimlilik Dergisi)
Purpose: The purpose of this paper is to empirically consider the effects of Total Factor Productivity (TFP), R&D, and income inequality on economic growth using panel data covering a broad range of developing and developed countries.Methodology: Panel data on relevant variables observed between 1998 and 2018 for 29 countries were analyzed. Cross-sectional dependence and stationarity tests of the variables were performed, then panel data regression models were tested and parameters were estimated. Then, the most appropriate model was determined and model assumptions such as autocorrelation, heteroskedasticity and cross-sectional dependence of model errors were tested. In all analyses, R statistical program was used.Findings: According to the analysis results, it has been determined that while productivity and R&D variables affect economic growth positively, increasing of income inequality also affects economic growth negatively.Originality: This research fills the gap in the literature in some ways: Our analysis covers a wider range of countries in both developing as well as developed countries, and emphasizes on recent period Gini coefficients, R&D expenditures, and productivity, from 1998 to 2018. Furthermore, the results of this research will not only facilitate the economic policymakers of the countries but will also be effective in realizing how important R&D expenditures and productivity are in economic growth.